Получение дисперсных материалов с микронными, субмикронными и наноструктурными частицами вещества при электрическом взрыве тонких металлических проводников - Баранов, М.И. (Електротехніка і електромеханіка, 2012)
Results of experimental research into formation of micron, submicron and nanostructured conductive products through electric explosion of thin copper wires in a technological chamber with process water are presented. It is shown that linear size of such fine-dispersed materials at maximum pulse conduction current density in the copper wires under 350 kA/mm² lies in the range of 10 nm through 10 μm.